Hubungan Pengetahuan Tentang Kanker Serviks terhadap Motivasi Wanita Usia Subur Melakukan Pemeriksaan Inspeksi Visual Asam Asetat (IVA) di Puskesmas Payangan - Ketut Ayu Lestari Windhradhi; Anny Eka Pratiwi; Dewa Ayu Putu Ratna Juwita (Detector: Jurnal Inovasi Riset Ilmu Kesehatan, 2025)
Cervical cancer remains a major public health problem and is one of the leading causes of cancer-related mortality among women in Indonesia. Early detection through Visual Inspection with Acetic Acid (VIA) is an effective and feasible screening method at the primary health care level. However, the coverage of VIA screening among women of reproductive age (WRA) remains low. Knowledge is considered an important predisposing factor that may influence women’s motivation to undergo VIA screening. This study aimed to analyze the association between cervical cancer knowledge and motivation to undergo VIA screening among women of reproductive age. This study employed a quantitative analytic design with a cross-sectional approach. A total of 105 women of reproductive age were recruited using consecutive sampling at the Payangan Community Health Center, Gianyar Regency, Indonesia. Data were collected using validated and reliable structured questionnaires measuring cervical cancer knowledge and motivation to undergo VIA screening. Univariate analysis was performed to describe respondent characteristics, while bivariate analysis using the chi-square test was applied to examine the association between knowledge and motivation at a significance level of 5%. The results showed that 61.9% of respondents had good knowledge of cervical cancer, while 52.4% demonstrated low motivation to undergo VIA screening. A statistically significant association was found between cervical cancer knowledge and motivation to undergo VIA screening (p = 0.043). Women with higher levels of knowledge tended to have greater motivation to participate in VIA screening. In conclusion, cervical cancer knowledge is significantly associated with motivation to undergo VIA screening among women of reproductive age. These findings suggest that strengthening health education interventions at primary health care facilities is essential to enhance motivation and increase participation in early cervical cancer detection programs.